Design, Synthesis and Biological Evaluation of Trimethine Cyanine Dyes as Fluorescent Probes for the Detection of Tau Fibrils in Alzheimer's Disease Brain and Olfactory Epithelium. Issue 6 (16th April 2013) - Gu, Jiamin; Anumala, Upendra Rao; Heyny‐von Haußen, Roland; Hölzer, Jana; Goetschy‐Meyer, Valérie; Mall, Gerhard; Hilger, Ingrid; Czech, Christian; Schmidt, Boris
Abstract : Shedding light on grey matter: Fluorescent trimethine cyanines were evaluated as imaging probes for neurofibrillary tangles in post‐mortem brain sections of Alzheimer's disease patients. These probes bind to neurofibrillary tangles with high contrast and selectivity over amyloid β plaques.